2021
DOI: 10.3390/cancers13061378
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Estimates of the Age-Specific Cumulative Risk of Breast Cancer for Pathogenic Variants in CHEK2: Findings from the Australian Breast Cancer Family Registry

Abstract: Case-control studies of breast cancer have consistently shown that pathogenic variants in CHEK2 are associated with about a 3-fold increased risk of breast cancer. Information about the recurrent protein-truncating variant CHEK2 c.1100delC dominates this estimate. There have been no formal estimates of age-specific cumulative risk of breast cancer for all CHEK2 pathogenic (including likely pathogenic) variants combined. We conducted a population-based case-control-family study of pathogenic CHEK2 variants (26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We previously calculated cumulative risk estimates for CHEK2 in the ABCFR and observed that the penetrance estimates for pathogenic variants in CHEK2 and ATM are not statistically different (Fig. 1) [8]. There is an urgent and currently unmet need to provide robust information that can inform risk management strategies for carriers of pathogenic variants in intermediate risk genes such Cumulative risk (%)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously calculated cumulative risk estimates for CHEK2 in the ABCFR and observed that the penetrance estimates for pathogenic variants in CHEK2 and ATM are not statistically different (Fig. 1) [8]. There is an urgent and currently unmet need to provide robust information that can inform risk management strategies for carriers of pathogenic variants in intermediate risk genes such Cumulative risk (%)…”
Section: Discussionmentioning
confidence: 99%
“…Bloodderived germline DNA from 1480 case probands and 864 control probands were screened by targeted-sequencing of the coding regions and proximal intron-exon junctions of BRCA1 (NM_007294.4), BRCA2 (NM_000059.4) and ATM (NM_000051.4). Details of study participant characteristics and selection, sequencing and data processing and variant filtering and annotation methods have been published previously [8] and are summarized in Additional file 1: Fig. S1.…”
Section: Study Participants and Genomic Data Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…PVs in BRCA1 and BRCA2 have frequencies of 0.21% and 0.31% in the European population [ 46 ], while the frequencies of ATM and CHEK2 PVs reach 1% [ 47 ] and 1.4% [ 48 ]. These estimations, taken together, and given the scarcity of double-heterozygotes reports, indicate that the prevalence of digenic coinheritance is likely underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates were adjusted for clinic-based ascertainment using the retrospective likelihood method [ 18 ]. For each gene, the cumulative risk (penetrance) to a given age was calculated as one minus the exponential of minus the cumulative incidence for carriers, which itself was the sum from age zero to the given age of the estimated HR multiplied by the non-carriers’ prostate cancer age-specific incidence [ 19 ]. Non-carrier incidences were set equal to the age-specific population incidence rates for Australia in the period 1998–2002 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%